Culture of pacu Piaractus mesopotamicus in biofloc technology (BFT): insights on dietary protein sparing and stomach content - Sgnaulin, Tayna; Pinho, Sara M [UNESP]; Durigon, Emerson Giuliani; Thomas, Micheli Cristina; de Mello, Giovanni Lemos; Emerenciano, Maurício Gustavo Coelho (Springer Nature, 2021)
The biofloc technology (BFT) is an intensive and sustainable production system, in which microorganisms can contribute to the maintenance of water quality and serve as a complementary food source for reared animals. The aim of this study was to evaluate three production strategies and whether the biofloc system enables the dietary reduction of crude protein (CP) levels for pacu (Piaractus mesopotamicus). For this purpose, pacu juveniles were reared in three treatments: clear water with 27% CP (CW-27), biofloc with 27% CP (BFT-27), and biofloc with 22% CP (BFT-22). Growth performance parameters were assessed, as well as the physicochemical parameters and planktonic community of the water, in addition to the proximate composition of carcasses. Complementarily, the stomach content of fish submitted to fasting in different feeding periods was evaluated. As for the growth performance, all variables evaluated were higher in BFT-27 and BFT-22 compared to CW-27, with an exception of the specific growth rate. No significant differences were found between the diets offered in the BFT systems. Several microorganisms were found in the BFT system, which might be directly related to the higher growth performance of fish in comparison to CW. Even though pacu is not considered a species with filtering habits, its consumption of bioflocs was evident through the evaluation of the stomach content of fish during 48 h. This study demonstrated the technical viability of cultivating pacu in BFT systems, with a possible reduction of dietary protein from 27 to 22% CP, without affecting the growth performance of animals.
Keywords: Microbial flocs; Microorganisms; Nutrition; Stomach content